Analisis Dampak Pernikahan Dini Terhadap Perceraian (Studi Kasus Di Kota Serang) - Nurwahyuni, Dwi; Elsiana (CV. Kurnia Grup, 2025)
High rates of early marriage indicate that the implementation and empowerment of government-recommended regulations are still low. This reflects the social phenomenon of early marriage in Serang City, stemming from simplistic thinking among its populace, perpetuating the issue through generations. This has significant implications, particularly on divorce rates. This research employs a descriptive qualitative approach, using both primary and secondary data. Informants were selected through purposive sampling, and data analysis utilized triangulation. The theory applied to analyze the issue relates to the relationship between early marriage and divorce. The study's findings indicate that there are still numerous cases of early marriage in Serang City, causing adverse impacts on individuals and society, including divorce. The Serang City government is committed to addressing and preventing early marriages through cross-sector collaboration. Effective collaboration across sectors is expected to reduce the practice of early marriage and decrease the overall divorce rate in Serang City